2014
DOI: 10.1007/s11408-014-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

(Un)skilled leveraged trading of retail investors

Abstract: We study the trading behavior of retail investors in the market of leveraged bank-issued retail derivatives designed to trade excessively, speculate and gamble on ongoing trends and market movements. We analyze whether retail investors have private information and benefit disproportionately or whether they gamble. We answer this question along three dimensions: (i) profitability, (ii) news trading, and (iii) sensitivity to implicit trading costs. We distinguish derivatives by the type of underlying (index vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…These results show that individual warrant investors are not as uninformed or irrational as recent literature (e.g., Meyer et al., ) suggests for other segments of the retail derivatives markets. A significant share of investors is able to compare prices and even margins, and incorporates this information into their investment decisions.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…These results show that individual warrant investors are not as uninformed or irrational as recent literature (e.g., Meyer et al., ) suggests for other segments of the retail derivatives markets. A significant share of investors is able to compare prices and even margins, and incorporates this information into their investment decisions.…”
Section: Resultssupporting
confidence: 73%
“…As the main reason for trading is speculation (see, e.g., Bauer et al, , Schmitz and Weber, , Meyer et al, , Rieger and Hens, ), investors are usually required to make timely decisions. Only in rare cases does an investor observe the pricing of a warrant over a series of dates.…”
mentioning
confidence: 99%
“…In the Netherlands, a study on options trading by retail investors concluded that most individuals incur substantial losses, with an average monthly negative return of −1.81% [72]. Profitability analysis of Germans trading leverage certificates of single stocks (which are structurally similar to CFDs) generated negative returns between −4.96% and −9.45% (for comparison, in the same period, the German stock index went up 30%); these products were also highly leveraged, with an average nine-fold increase in volatility and risk-taking, with every 1% move in asset prices translating into a 9% gain or loss for the investor [73]. High amounts of leverage have also been blamed for the losses experienced by more than 80% of clients trading CFDs [74].…”
Section: Why Investing In High-risk Derivatives Is a Losing Strategymentioning
confidence: 99%
“…The reason for the first is that market makers do not have to balance demand and supply as they can satisfy any demand quantity because they issue the product themselves and simply "close" the certificate when it is sold back. The reason for the latter is that most investors in this market segment are uninformed (Meyer et al, 2013;Schroff et al, 2013). Even if an investor was informed, the resulting risk for the market maker is negligible as he hedges the certificate when an order arrives.…”
Section: Market Design and Model 21 Market Designmentioning
confidence: 99%
“…Recent empirical findings suggest that individual investors act uninformed in this market (Meyer et al, 2013;Schroff et al, 2013) and that the issuers' pricing policy is-besides standard behavioral biases-the key reason for investors' negative returns in short-term certificates (Entrop et al, 2012) and poor risk-adjusted performance in long-term certificates (Entrop et al, 2013a). In fact, theoretical models imply that investors' demand for certificates can hardly be justified by standard preferences (Breuer and Perst, 2007;Branger and Breuer, 2008;Bernard 1 Other studies reporting overpricing include for the US Chen and Kensinger (1990); Chen and Sears (1990); Baubonis et al (1993); Benet et al (2006), for Germany Stoimenov and Wilkens (2005); Muck (2006); Wilkens and Stoimenov (2007); Baule et al (2008); Baule (2011); Baule and Tallau (2011), for Switzerland Wasserfallen and Schenk (1996); Burth et al (2001); Grünbichler and Wohlwend (2005); Wallmeier and Diethelm (2009), and for the Netherlands Szymanowska et al (2009).…”
Section: Introductionmentioning
confidence: 99%